Towards spark-proof gaseous pixel detectors. (15th November 2016) - Tsigaridas, S.; Beuzekom, M.v.; Chan, H.W.; Graaf, H.v.d.; Hartjes, F.; Heijhoff, K.; Hessey, N.P.; Prodanovic, V.
Abstract: The micro-pattern gaseous pixel detector, is a promising technology for imaging and particle tracking applications. It is a combination of a gas layer acting as detection medium and a CMOS pixelated readout-chip. As a prevention against discharges we deposit a protection layer on the chip and then integrate on top a micromegas-like amplification structure. With this technology we are able to reconstruct 3D track segments of particles passing through the gas thanks to the functionality of the chip. We have turned a Timepix3 chip into a gaseous pixel detector and tested it at the SPS at Cern. The preliminary results are promising and within the expectations. However, the spark protection layer needs further improvement to make reliable detectors. For this reason, we have created a setup for spark-testing. We present the first results obtained from the lab-measurements along with preliminary results from the testbeam.